2017
DOI: 10.1037/aca0000101
|View full text |Cite
|
Sign up to set email alerts
|

Beauty for the eye of the beholder: Plane pattern perception and production.

Abstract: Visual patterns are a key phenomenon in human aesthetics, reflecting a human "sense of order" (Gombrich, 1984). Social effects on the producer of visual aesthetic output may shed light on intuitive aesthetic knowledge that laypeople can utilize without explicit instructions, with implications for the evolution of aesthetics in humans more generally. We apply all 3 methods suggested by Gustav Fechner (preference, production, and use; Fechner 1871, 1876) to visual geometrical patterns, showing that symmetrical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In social and cognitive psychology, it is a common problem that stimuli on which researchers test their predictions may not be representative of a general population of these stimuli, which can lead to biased findings (Westfall et al, 2015). To our knowledge, in previous research on beauty, various stimuli were used, from patterns to images (e.g., Forsythe et al, 2011; Newman & Bloom, 2012; Pelowski et al, 2018; Westphal-Fitch & Fitch, 2017). These stimuli were typically created by following a certain rationale or selected from websites or among various artworks, but it was not considered whether they exemplify the entire stimuli population to which they belong.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In social and cognitive psychology, it is a common problem that stimuli on which researchers test their predictions may not be representative of a general population of these stimuli, which can lead to biased findings (Westfall et al, 2015). To our knowledge, in previous research on beauty, various stimuli were used, from patterns to images (e.g., Forsythe et al, 2011; Newman & Bloom, 2012; Pelowski et al, 2018; Westphal-Fitch & Fitch, 2017). These stimuli were typically created by following a certain rationale or selected from websites or among various artworks, but it was not considered whether they exemplify the entire stimuli population to which they belong.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that a key factor is the patterns’ randomness. Disordered images are generally perceived as less beautiful than the ordered ones (e.g., Bertamini et al, 2013; Makin et al, 2012; Westphal-Fitch & Fitch, 2017). Within our aesthetic quality model, we posit that this is the case because disorder is associated with chance and the absence of creative process that requires skill (Falk & Konold, 1997; Gabriel & Quillien, 2019; Serafin et al, 2011).…”
Section: Aesthetic Quality Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent study using frieze-like stimuli also finds an order preference. Westphal-Fitch and Fitch (2017) had participants rate bench tile patterns with translational, reflectional and rotational symmetry (low entropy scores) and those with random patterning (high entropy scores). Observers preferred symmetric tiles.…”
Section: The Aesthetics Of Frieze Patterns: Effects Of Symmetry and M...mentioning
confidence: 99%
“…However they also found individual differences in which some of the participants preferred non-symmetric patterns. Westphal-Fitch and Fitch (2017) found that symmetrical geometric patterns were rated significantly more attractive than random patterns. Westphal-Fitch and Fitch (2013) looked at preferences for "crazy quilts," those intended to appear haphazard and unstructured.…”
mentioning
confidence: 96%